Management skozi prizmo digitalnega in zelenega prehoda v družbo 5.0 (University of Maribor Press, 2025)
Management Through the Lens of the Digital and Green Transition into Society 5.0. The scientific monograph Management Through the Lens of the Digital and Green Transition into Society 5.0 covers areas primarily related to the field of management in connection with various aspects of employee management and broader societal issues. The content of the monograph includes topics such as human resource management and the sustainable development of employees, ethical decision-making in management, as well as management in healthcare, education, and critical infrastructure, all within the context of the digital and green transition into Society 5.0. The monograph is up to date and responds to the need for connecting scientific content with practical applications. The chapters of this scientific monograph, which incorporate an appropriate level of interdisciplinarity, will serve as a springboard for the study and advancement of knowledge for students, the academic community, and society at large.